2018
DOI: 10.1177/0300985818798094
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Thickness and Modified Clark Level in Canine Cutaneous Melanocytic Tumors

Abstract: Breslow thickness and Clark level are prognostic factors for human cutaneous melanomas. Breslow thickness is measured with an ocular micrometer from the top of the granular layer of the epidermis to the deepest invasive cell across the broad base of the tumor, while Clark level is based on the anatomical level of invasion through the layers of the dermis. Because of the anatomical differences between humans and dogs, we evaluated the tumor thickness and a modified Clark level in 77 canine primary cutaneous mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(63 citation statements)
references
References 20 publications
1
62
0
Order By: Relevance
“…Usually, surgical resection is curative [32,33,34,87,89], although some pathological characteristics, such as a mitotic index ≥3 over ten fields (otf) the presence of ≥20 nuclear atypia, a Ki67 index >15%, ulceration, lymphatic invasion, and tumors extending beyond the dermis, have a negative influence on prognosis [33,35,37,90,91]. More recently, Silvestri et al showed that Breslow thickness is significantly associated with histological malignancy, clinical outcome, and presence of recurrence/metastasis [93].…”
Section: Canine Cutaneous Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, surgical resection is curative [32,33,34,87,89], although some pathological characteristics, such as a mitotic index ≥3 over ten fields (otf) the presence of ≥20 nuclear atypia, a Ki67 index >15%, ulceration, lymphatic invasion, and tumors extending beyond the dermis, have a negative influence on prognosis [33,35,37,90,91]. More recently, Silvestri et al showed that Breslow thickness is significantly associated with histological malignancy, clinical outcome, and presence of recurrence/metastasis [93].…”
Section: Canine Cutaneous Melanomamentioning
confidence: 99%
“…Cutaneous melanoma has a relatively benign behavior in dogs. Recent studies, evaluating outcomes after surgical excision, showed that the MST was 1363 days and not reached with 77%–88% of dogs alive at 1 year and 54% alive at 2 years [36,39,40,93,94] (Figure 2). In the series of 87 dogs (Laver et al, 2018), 12% of dogs had lymph node metastases and 3.7% had pulmonary metastases at diagnosis.…”
Section: Canine Cutaneous Melanomamentioning
confidence: 99%
“…Samples in this study were partially included in a previous study on the usefulness of tumor thickness and modified Clark level for the evaluation of canine melanocytic tumors. 11 All samples were histologically evaluated for the parameters having the greater validity for prognostic use in canine melanocytic neoplasia, according to the current literature. 10,11…”
Section: Histologic Examinationmentioning
confidence: 99%
“…11 All samples were histologically evaluated for the parameters having the greater validity for prognostic use in canine melanocytic neoplasia, according to the current literature. 10,11…”
Section: Histologic Examinationmentioning
confidence: 99%
See 1 more Smart Citation